Efektifitas Penggunaan Strategi Pembelajaran Card Sort Dalam Meningkatkan Kemampuan Membaca Al-Qur'an Pada Anak di TPA Sidomulyo Kota Palangka Raya - Nadira Nadira Fajri; Hamidah Hamidah; Muhammad Redha Anshari (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research departs from the curiosity to measure and find out the effectiveness of learning strategies in teaching al-Qur'an learning materials in improving the ability to read the Qur'an by conducting experimental research with strategies that have never been carried out before in the research place, namely the card sort learning strategy. to children at the Sidomulyo TPA, Palangka Raya. The research used a quantitative method research approach, with the type of research design being a one-group pretest-posttest design by conducting pretest and posttest. The population used is all students at TPA Sidomulyo with the type of sample being total sampling. Data collection techniques used pretest and posttest and data analysis techniques were tested with normality test, paired sample test. The results showed that (1) the use of card sort learning strategies can make the classroom atmosphere more active than passive, not monotonous and make children remember the learning materials that have been explained. (2) The significance value of 0.200 > 0.05 has been obtained. So it can be concluded that the residual value is normally distributed. Furthermore, the data is tested and the results obtained from the paired sample test are 0.00 > 0.05, so it can be concluded that there is a significant effectiveness of using the card sort learning strategy in improving the ability to read the Qur'an.